Body size estimation and weight management practices in urban poor communities in Ghana: A cross-sectional study - Grace Agyemang FREMPONG; John K. ANARFI; Delali Margaret BADASU; Samuel Nii Ardey CODJOE (Journal of Health and Social Sciences)
Introduction: Body size perception is a pertinent issue globally due to its implications for weight mana- gement. This study examined the influence of body size estimation on weight management behaviours in urban poor areas of Ghana. Methods: A cross-sectional design was used to collect data among a sample of 395 adults aged 18-70 years. A semi-structured questionnaire was designed for collection of data on socio-demographic characteristics, weight perceptions, and weight management strategies. Anthropometric measurements were also taken, using standard procedures. Logistic regression models were used to examine relationships among the va- riables. Results: More than half (57%) of the total sample was overweight or obese and 56.7% of the participants accurately estimated their body size. Nearly a third (37%) of the participants intended to stay about the same weight, while 29.6% and 11.9% wanted to lose or gain weight, respectively. To achieve their weight management goals, 60.3% of the participants engaged in healthy weight management practices. Body size estimation had no statistically significant relationship with weight management practices. However, the likelihood of engaging in healthy practices increased as age increased (OR = 1.021; 95% CI: 1.000 to 1.042). Individuals who belonged to households of upper wealth category were less likely than those in lower wealth households to engage in healthy practices (OR = 0.548; CI: 0.330 to 0.911). Community of residence, a community conducive to physical activity and social support also significantly predicted weight management practices. Conclusion: The findings of this study highlight the importance of age and some socio-environmental factors in public health strategies for weight management.